Novas fontes de custeio do transporte público urbano: Princípios e potencialidades - Carlos Henrique Ribeiro de Carvalho; Vander Mendes Lucas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This article deals with a study on the different ways of financing the cost of urban public transport services. In Brazil, the financing of public transport is only supported by fare collection, which brings great social inequities and a financial crisis to the system. The authors defend tariff diversification based on Pigouvianand progressive payment principles, among others. Based on this discussion is possible identify new sources of funding and calculate their collection potential for public transportation.
10419/284880
Keywords: R48; 330; mass transit fare; public transportation funding